Canola : chemistry, production, processing, and utilization - Daun, James K.; Eskin, N. A. M.; Hickling, Dave (AOCS monograph series on oilseeds, 2011)
The book gives a picture of the canola crop including its history, botany, genetics, distribution, breeding and biotechnology, production, processing, composition, nutritional properties and utilization of the seed, oil and meal, as well as an economic profile. While the main focus in this book is on canola of Canadian origin, its cousin crop oilseed rape will also be discussed to a lesser extent. The work provides up to date information on the crop and highlights areas where research and development is either needed or is in process.